Evaluation of the Impact-R for monitoring the platelet storage lesion. - Albanyan, A; Murphy, M; Harrison, P (2009)
The aim of this study was to evaluate the Impact-R test for measuring changes in platelet function in stored platelet concentrates. Platelet function was measured within samples (reconstituted with red cells) taken from apheresis concentrates (n = 20) and buffy coat concentrates (n = 20) stored for up to 7 days. The final mean platelet counts and haematocrits in apheresis concentrates were 319 x 10(9)/l and 56.2%, and in buffy coat concentrates they were 296 x 10(9)/l and 54.6%, respectively. The surface coverage (a measure of adhesion) decreased significantly during storage of PCs from 11.6 +/- 4 and 8.5 +/- 3.8% on day 1 to 7.4 +/- 3.4 and 5.9 +/- 3% on day 7 in apheresis and buffy coat concentrates, respectively. Buffy coat concentrates exhibited a significantly lower surface coverage than apheresis concentrates on day 1 of testing. The average size (a measure of aggregation) also decreased significantly during storage from 26.9 +/- 3.7 microm(2) and 24.1 +/- 3.1 microm(2) on day 1 to 21.8 +/- 3 microm(2) and 20.8 +/- 2.2 microm(2) on day 7 in apheresis and buffy coat concentrates, respectively. However, in contrast to the surface coverage, no significant difference in the average size between the two types of concentrate was observed. In conclusion, both platelet adhesion and aggregation measured by the Impact-R device decline significantly during the storage of platelet concentrates. The Impact-R is a simple device to perform rapid test which may be useful for the assessment of platelet function within platelet concentrates.